2011
DOI: 10.25100/iyc.v5i2.2298
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulación de Aditivos para la Industria de Alimentos

Abstract: La encapsulación es una técnica que se emplea para proteger los aditivos utilizados en la industria de alimentos, la conservación, fortificación y liberación controlada en el tiempo de nutrientes, disminución de la higroscopicidad, transformación de sabores líquidos a polvos, estabilidad durante el almacenamiento, mejoramiento de cualidades organolépticas y funcionales de productos alimenticios, etc. Los principales aditivos encapsulados en la industria de alimentos son: ácidos, colorantes, pigmentos, enzimas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This same trend was also observed for betacyanins (Figure 9) and betaxanthins (Figure 10) Albarran-Corona (2023) mentions that the release of the active compound in the microcapsule is influenced by the concentration gradient and the attractive forces between chains, such as hydrogen bridges, Van der Waals forces, degree of crosslinking and crystallinity. In addition, the release is controlled by the solubility and permeability of the core material in the protective material, while Aldana et al (2004) mentions that the stability of the capsule depends on the transition temperature of the capsule. The stability of the capsule depends on its transition temperature being higher than the storage temperature.…”
Section: Kinetics Of Betalains Release From Microcapsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…This same trend was also observed for betacyanins (Figure 9) and betaxanthins (Figure 10) Albarran-Corona (2023) mentions that the release of the active compound in the microcapsule is influenced by the concentration gradient and the attractive forces between chains, such as hydrogen bridges, Van der Waals forces, degree of crosslinking and crystallinity. In addition, the release is controlled by the solubility and permeability of the core material in the protective material, while Aldana et al (2004) mentions that the stability of the capsule depends on the transition temperature of the capsule. The stability of the capsule depends on its transition temperature being higher than the storage temperature.…”
Section: Kinetics Of Betalains Release From Microcapsulesmentioning
confidence: 99%
“…Garambullo, whose scientific name is Myrtillocactus geometrizans, is a cactus (Nava-Martinez, 2023). It is widely distributed in central Mexico and, according to studies, it has been shown that garambullo can be considered a functional food because of its content of bioactive compounds, which are hypoglycemic and hypocholesterolemic (Aldana et al, 2004). Among these phytochemical compounds are betalains, which have important properties such as pigmentation (Otálara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of essential oils involves several problems, since, if these are applied directly to the surface of a product, the functional components can diffuse rapidly inward, subtracting protection from the surface. In addition, essential oils have a very intense flavor; consequently, a suitable technique must be selected for the implementation of the essential oils in food systems (Sandoval et al, 2004;Lakkis, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative is the addition of MOEO encapsulated by emulsification; this technique allows the delay of the chemical degradation of essential oils after being exposed to environmental factors such as light, oxygen, heat, among others. It not only protects the compound of interest, this technique could be used to mask the taste, increase the shelf life of the product, or to promote the controlled release of encapsulated components (Sandoval et al, 2004;Lakkis, 2007;Bakry et al, 2016).…”
Section: Introductionmentioning
confidence: 99%